1997
DOI: 10.1016/s0022-5347(01)64788-8
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Pubococcygeus Muscle in Urinary Continence in the Male Rat

Abstract: The role of the male rat pubococcygeus muscle (Pcm) in the micturition reflex was analyzed. Anatomical features of Pcm, electrical stimulation of its nerve, electrical recording and stimulation of the muscle and cystometrograms were carried out. Results showed that Pcm has fibers attached to the ventrolateral part of the external urethral sphincter, and that its activity contributes to hold the tail in the midline. Pcm shows activity during fluid expulsion in cystometrograms and spontaneous micturitions. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 12 publications
2
24
0
Order By: Relevance
“…Pcm location close to the midline of the body, its insertion into the sacral vertebrae, and its participation in micturition (Manzo et al, 1997), ejaculation (Manzo et al, 2000), and tail posture (Martinez-Gomez et al, 1992) are characteristics that allows us to consider the Pcm as an epaxial muscle; thus, implying that when compared to castration, denervation effect in epaxial muscles is not as strong as it is in striated muscles of limbs. Another possible explanation is that most studies of limb muscles were carried out in a separate way, that is through bilateral denervation in which besides the evident lack of muscle activity, environmental factors such as hormonal status, feeding behavior, mobilization, and a different muscular blood flow supply could be involved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pcm location close to the midline of the body, its insertion into the sacral vertebrae, and its participation in micturition (Manzo et al, 1997), ejaculation (Manzo et al, 2000), and tail posture (Martinez-Gomez et al, 1992) are characteristics that allows us to consider the Pcm as an epaxial muscle; thus, implying that when compared to castration, denervation effect in epaxial muscles is not as strong as it is in striated muscles of limbs. Another possible explanation is that most studies of limb muscles were carried out in a separate way, that is through bilateral denervation in which besides the evident lack of muscle activity, environmental factors such as hormonal status, feeding behavior, mobilization, and a different muscular blood flow supply could be involved.…”
Section: Discussionmentioning
confidence: 99%
“…In male rats, this muscle is not part of the levator ani complex (Yuan et al, 2003); however, its participation in micturition and ejaculation is highlighted through behavioral studies (Manzo et al, 2000) and by electrical stimulation of its nerve (Manzo et al, 1997). Furthermore, by analyzing the cross-sectional area of its fibers, we have shown that this muscle is sensitive to gonadal hormones (Alvarado et al, 2008), but we still do not know whether this effect is due to a direct action of these hormones on its fibers and/or through the neuromuscular complex, in which hormonal changes affect soma size, synaptic efficiency, and neuromuscular junction size of muscles such as the bulbocavernosus and levator ani (Breedlove and Arnold, 1981;Balice-Gordon et al, 1990;Tanaka and Arnold, 1993).…”
mentioning
confidence: 99%
“…In addition, preclinical studies focused on the role of the pelvic musculature in micturition are scarce and results are conflicting. In male rats, activity of the Pcm occurs during micturition (Manzo et al, 1997). However, this result was not replicated in female rats (Jiang et al, 2010).…”
Section: The Laboratory Ratmentioning
confidence: 87%
“…For example, the Pcm activity shown during the storage phase is a major component in the mechanism of urinary continence, because the electrical stimulation inhibits the bladder contraction and the urine output (Alves et al, 2011;our unpublished results). This is possible because the contraction of the Pcm during voiding is produced by the discharge of some of its afferents (from muscle spindles or tendon organs), sending information to both sacral 2 and 4 to modulate the activity of parasympathetic neurons (Manzo et al, 1997;Thor & de Groat, 2010). The Bsm and Ism activity during the voiding is mediated by a reflex called the urethrocorporocavernosal reflex.…”
Section: Pelvic-and Perineal-muscle Activities During Micturitionmentioning
confidence: 99%
“…Although in rats the Pcm is not considered part of the levator ani complex (Poortmans and Wyndaele, 1998;Yuan et al, 2003), it performs similar functions as in humans. It originates from the inner face of the pelvic bone at the level of the acetabulum and inserts in the third and fourth caudal vertebrae (Manzo et al, 1997), its fibers are attached in part to the ventrolateral portion of the external urethral muscular complex , and it is innervated by means of the somatomotor branch of the pelvic nerve (s-mbPn; Manzo et al, 1997). In male rats, Pcm plays an important role in the micturition process, regulating bladder tension during voiding and triggering a spinal reflex mechanism promoting continence (Manzo et al, 1997).…”
mentioning
confidence: 99%